2021
DOI: 10.3390/jcm10184037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nucleocapsid Protein Antigen Detection for Safe End of Isolation of SARS-CoV-2 Infected Patients with Long Persistence of Viral RNA in Respiratory Samples

Abstract: Background. In SARS-CoV-2 infection, viral RNA may persist in respiratory samples for several weeks after the resolution of symptoms. Criteria to assess the end of infectivity are not unequivocally defined. In some countries, time from diagnosis is the unique criterion used, in addition to symptom cessation. This study evaluates the role of the Lumipulse® Antigen Assay (LAA) for the safe end of isolation of patients ≥21 days after the diagnosis of infection. Methods. A total of 671 nasopharyngeal swabs from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Previous studies’ findings supported us to adopt SARS-CoV-2 sgRNA RT-PCR as the reference method for our antigen tests’ assessment [ 6 , 15 , 16 , 17 ]. One study [ 15 ] using respiratory tract samples obtained from COVID-19 patients within 7 days of symptom onset showed the correlation between the SARS-CoV-2 antigen (using the Becton Dickinson BD Veritor System for Rapid Detection of SARS-CoV-2 test) and SARS-CoV-2 culture (using a VeroE6TMPRSS2 cell line-based high-sensitive culture test) positivity.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies’ findings supported us to adopt SARS-CoV-2 sgRNA RT-PCR as the reference method for our antigen tests’ assessment [ 6 , 15 , 16 , 17 ]. One study [ 15 ] using respiratory tract samples obtained from COVID-19 patients within 7 days of symptom onset showed the correlation between the SARS-CoV-2 antigen (using the Becton Dickinson BD Veritor System for Rapid Detection of SARS-CoV-2 test) and SARS-CoV-2 culture (using a VeroE6TMPRSS2 cell line-based high-sensitive culture test) positivity.…”
Section: Discussionmentioning
confidence: 69%
“…This study showed that SARS‐CoV‐2 could not be cultured from specimens yielding RT‐PCR positive and SARS‐CoV‐2 antigen assay negative results, and the data suggested that patients with RT‐PCR‐proven COVID‐19 testing negative by SARS‐CoV‐2 antigen assay are unlikely to be infectious 34 . Other studies have also confirmed that there is a certain relationship between the amount of SARS‐CoV‐2 antigen and the infection status and virus shedding 51–55 . However, this specific connection needs to be explored continuously.…”
Section: Introductionmentioning
confidence: 85%
“… 34 Other studies have also confirmed that there is a certain relationship between the amount of SARS‐CoV‐2 antigen and the infection status and virus shedding. 51 , 52 , 53 , 54 , 55 However, this specific connection needs to be explored continuously.…”
Section: Introductionmentioning
confidence: 99%